Mutation status of RAD51C, PALB2 and BRIP1 in 100 Japanese familial breast cancer cases without BRCA1 and BRCA2 mutations. Issue 11 (18th September 2017) - Sato, Katsutoshi; Koyasu, Mio; Nomura, Sachio; Sato, Yuri; Kita, Mizuho; Ashihara, Yuumi; Adachi, Yasue; Ohno, Shinji; Iwase, Takuji; Kitagawa, Dai; Nakashima, Eri; Yoshida, Reiko; et al.
Abstract : In addition to BRCA1 and BRCA2, RAD51C, PALB2 and BRIP1 are known as breast cancer susceptibility genes. However, the mutation status of these genes in Japanese familial breast cancer cases has not yet been evaluated. To this end, we analyzed the exon sequence and genomic rearrangement of RAD51C, PALB2 and BRIP1 in 100 Japanese patients diagnosed with familial breast and ovarian cancer and without BRCA1 and BRCA2 mutations. We detected a large deletion from exons 6 to 9 in RAD51C, 4 novel BRIP1 missense variants containing 3 novel non‐synonymous variants, c.89A>C, c.736A>G and c.2131A>G, and a splice donor site variant c.918+2T>C. No deleterious variant of PALB2 was detected. The results of pedigree analysis showed that the proband with a large deletion on RAD51C had a family history of both breast and ovarian cancer, and the families of probands with novel BRIP1 missense variants included a male patient with breast cancer or many patients with breast cancer within the second‐degree relatives. We showed that the mutation frequency of RAD51C in Japanese familial breast cancer cases was similar to that in Western countries and that the prevalence of deleterious mutation of PALB2 was possibly lower. Furthermore, our results suggested that BRIP1 mutation frequency in Japan might differ from that in Western countries. Abstract : The carrier frequency of RAD51C deleterious mutation in Japanese was similar to that in other countries, and its significance for PALB2 was possibly lower. On the other hand, observation of 4 novel BRIP1 mutations, 3 of these mutation identified in the family with male breast cancer onset, suggested that BRIP1 mutation status in Japan might be different from that in Western countries.